Rancang Bangun Prototype Monitoring Instalasi Pengolahan Air Limbah (IPAL) Di Suwung Berbasis Internet of Things - Maulidin, Mohammad Putra; Gusri, Khaeril; Dzaudan, Daffa; Jasa, Lie; Wijaya, Arta (Majalah Ilmiah Teknologi Elektro; Vol 24 No 1 (2025): ( Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2025)
Wastewater management is a critical component of environmental sustainability, particularly in regions undergoing rapid industrial development such as Bali. The Wastewater Treatment Plant (IPAL) in Suwung plays an essential role in ensuring that effluents meet environmental quality standards mandated by regional and national regulations. However, current monitoring practices at the facility are conducted manually, resulting in potential delays in pollution detection and timely decision-making. This study proposes the design and implementation of an Internet of Things (IoT)-based prototype for real time wastewater quality monitoring. The system integrates multiple sensors-including pH, temperature, turbidity, and water level sensors-controlled by an arduino UNO microcontroller and ESP 32 module. Measurement data are transmitted to Blynk and ThingSpeak platforms in real time, stored in a data logger for further analysis, and made accessible via a web-based monitoring interface. The results demonstrate that the system is capable of delivering accurate and real time data, which can support more efficient monitoring and facilitate timely environmental management decisions. This prototype offers a reliable and scalable solution for digitizing wastewater monitoring processes in treatment facilities